ACADEMIC CONFERENCES AND THEIR MULTIFACETED BENEFITS AND ROLES IN THE NIGERIAN CONTEXT (Journal of Association of Educational Management and Policy Practitioners, 2025)
This chapter elucidates the integral role of academic conferences within the Nigerian scholarly landscape, perusing its multifarious benefits and the prevailing realities that shape its effectiveness. While academic conferences are ostensibly platforms for knowledge dissemination and networking, Academic conferences contribute far beyond mere academic engagement, fostering innovation, collaboration, and the elevation of Nigeria's academic reputation on the global stage. Through a comprehensive analysis of extant literature, qualitative interviews, and case studies, this discourse seeks to elucidate the nuanced dynamics of academic conferences in Nigeria, thereby contributing to a deeper understanding of their significance in the broader context of educational development. This chapter delves into the multifaceted benefits of academic conferences within the Nigerian context, encompassing enhanced research collaboration, capacity building, and networking opportunities and the challenges that hinder effective conference organization and participation in Nigeria.